(untitled) - Cass Lubisi; Cass Lubisi; Ben Parker; Volker Wedekind (Oxford, 1999)
This series of mixed-media learning packages explores the implications of an outcomes- or competence-based educational philosophy for the practice of learning and teaching in South Africa. The series is a dramatic departure from the often didactic and alienating educational texts produced in the past. Each module develops - through case-studies, school-based dialogues, and common educational problems - teachers' abilities to think and solve problems in the fluid educational environment in which they find themselves
Keywords: Competency based education; Teaching